Women's Labor Migration and Gender Nexus (A Study of Migrant’s Families in Pokhara, Nepal) - Chaudhary, Anchala; Pokhrel , Shreedhar (Journal of Interdisciplinary Studies, 2024)
The study aimed to investigate and analyze the effects of the global market on gender practices. Women's labor migration has multifaceted effects on families. In Nepal, there have been increasing trends of women's labor migration in the last ten years, i.e., from 8595 in 2008/2009 to 20578 in 2018/2019, as per the Nepal Labor Migration Report 2020. The mobility of women's migration doesn’t only boost national income but also makes women self-reliant. In Nepal’s traditional society and culture, this cumulative trend of women's migration has created new discourse in gender practices. So, this study aims to investigate the reconstruction of gender roles and responsibilities and the shifting pattern of power in a household's structure. Data from both primary sources and secondary literature is used to support the arguments. The study is guided by feminist standpoint theory and Marxian theory. The data were purposefully selected from 198 households of women's migrant families in Pokhara, Nepal in 2022. Both quantitative and qualitative methods were used to gather the information. The finding reveals that the traditional patriarchal mode of society is changing, where women are more dependent on men for their survival. Not only migrant women, but the women left behind, who act as proxy managers, are playing a crucial role in household formation and decision-making. The various forms of capital gained in transnational space have not only changed cultural ideologies about gender practices but also assured women’s freedom, independence, and confidence in the public sphere of life.